“IT’S MORE BAD THAN GOOD, THERE’S A LOT TO IMPROVE” FOR TRANSVESTITES AND TRANSSEXUALS (Interdisciplinary Studies Journal, 2025)
Brazil, recognized as a multicultural country full of diversity, is also unequal and exclusionary. Considering this panorama, this study aims to verify how is the current Brazilian scenario for transvestites and transsexuals from the perspective of the reality experienced by them in the metropolitan region of Porto Alegre. Methodologically, this is an exploratory and descriptive study, with a qualitative approach and a technical field research procedure. The participants were selected based on Snowball sample, were interviewed, and narrated their experiences and conceptions about the reality of transgender people in the Brazilian context. The results, examined using the assumptions of Bardin's content analysis, indicate that, gradually, a protective legal framework was built for transvestites and transsexuals, however, in practice, this has proven to be ineffective, given that such subjects face the most diverse difficulties in all spectrums of their life, being subjected to a society that does not accept differences and, consequently, excludes and marginalizes those who deviate from the standards imposed by it. It is possible to conclude that this process causes social suffering, making it clear that laws and public policies do not always materialize on a material level, therefore, is necessary to achieve their effectiveness.
Keywords: Social Inequality; Exclusion; Public Policies; Transvestites and Transsexuals